Classificatory Smoothing of Income with Extraordinary Items: Research Implications. - Barnea, Amir; Ronen, Joshua; Sadan, Simcha (The Accounting Review, 1977)
Abstract The article discusses implications of a study conducted on the idea of classificatory smoothing of income statement statistics other than net income. The study was investigated on a hypothesis using correlational analysis without data on managements' intentions, it sought only to establish that managements behaved as if smoothing were intended. A central issue is the set of hypotheses to be tested in empirical research on income smoothing. Researchers of the study do not address the primary question of whether income smoothing exists. Instead, they attempt to determine if correlation patterns suggest one sort of smoothing rather than another. However, just the possibility of classificatory smoothing makes apparent some fundamental problems in income smoothing research and in the study of as-if smoothing hypothesis. Those problems, which include correlation and data problems and the issue of management intention, are the subject of this article. Suggestions for improvements in income smoothing research also are made.